Phytochemical Screening and Determination of Total Flavonoid Content of Keji Beling Leaves Ethanol Extract (Strobilanthes crispa Bl.) - Mahyantika, Seftya Putri; Husain, Muhammad Hafizh; Nirwana, Linggar; Aldina, Devana Rahma; Gemilang, Satria; Nafisa, Nafisa; Ramadhan, Majida; Sjakoer, Nour Athiroh Abdoes; Faisal, Faisal (Biology, Medicine, & Natural Product Chemistry, 2025)
This study aims to determine the total flavonoid content in the ethanol extract of keji beling (Strobilanthes crispa) leaves using the UV-Vis spectrophotometric method with AlCl3 reagent. The research process includes maximum wavelength testing, preparation of quercetin standard solution, and analysis of total flavonoid levels. The results showed that the total flavonoid content in the extract was 144.347 ± 134.854 mg QE/g extract, with an extract yield of 0.4% and extract moisture content of 5.256%, which showed good potential in preventing the growth of microorganisms. Phytochemical screening revealed the presence of alkaloids, flavonoids, and tannins, while saponins, triterpenoids, and steroids were not detected. These findings confirm the importance of secondary metabolite compounds in plants and the potential of keji beling leaf extract as a source of active compounds with health benefits, including antioxidant and antibacterial activities. This study provides a basis for further research into the medical applications of this plant extract.